2020
DOI: 10.1186/s12939-020-01194-4
|View full text |Cite
|
Sign up to set email alerts
|

Salutogenic model of health to identify turning points and coping styles for eating practices in type 2 diabetes mellitus

Abstract: Background: It is important for people with Type 2 Diabetes Mellitus (T2DM) to eat healthily. However, implementing dietary advice in everyday life is difficult, because eating is not a distinguishable action, but a chain of activities, embedded in social practices and influenced by previous life experiences. This research aims to understand why and how eating practices are developed over the life-course by investigating influential life experiencesturning pointsand coping strategies for eating practices of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 102 publications
(124 reference statements)
3
13
0
Order By: Relevance
“…And there were significant differences in anxiety, sense of security, and disordered eating behaviors between positive coping style and negative coping style. These results correspond to previous research findings, which have indicated negative coping style could lead to more severe disordered eating behaviors [ 20 ], higher level of anxiety [ 21 ], and lower sense of security [ 22 ]. Next, when analyzing the mediating roles of anxiety and sense of security between coping style and disordered eating behaviors, we found an overall mediating role of 71.8%.…”
Section: Discussionsupporting
confidence: 92%
“…And there were significant differences in anxiety, sense of security, and disordered eating behaviors between positive coping style and negative coping style. These results correspond to previous research findings, which have indicated negative coping style could lead to more severe disordered eating behaviors [ 20 ], higher level of anxiety [ 21 ], and lower sense of security [ 22 ]. Next, when analyzing the mediating roles of anxiety and sense of security between coping style and disordered eating behaviors, we found an overall mediating role of 71.8%.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, approximately one fifth of our sample reported increased motivation to improve their diet due to the pandemic. These findings add to the evidence base suggesting significant life events such as a disease diagnosis or becoming a parent are associated with improved eating behaviors (Polhuis et al, 2020 ). In contrast to previous studies (Chopra et al, 2020 ; Hu et al, 2020 ; Knell et al, 2020 ), the best-represented TM in our study related to improving physical activity, with a quarter expressing greater motivation to increase their activity.…”
Section: Discussionsupporting
confidence: 56%
“…Events that endanger positive expectations about their future self are usually experienced as most relevant to individuals, which in turn evoke greater behavioral responses (Aspinwall and Brunhart, 1996 ; McBride et al, 2003 ). In an extensive qualitative study, it was explained that major life events impacted an individual's outlook on life and thereby made them increasingly thoughtful regarding the effects of their current diet (Polhuis et al, 2020 ). Our finding that a higher level of altered self-concept was associated with increased intentions toward behavioral change provides evidence that the COVID-19 crisis induces a comparable effect.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circumstances change over time, as do lifestyle factors. Unforeseen, traumatic or positive events have additional impacts on lifestyle choices, such as eating habits, thereby influencing the adherence to recommendations [ 13 ]. Additionally, public health measures and policies to promote healthy lifestyles, such as anti-smoking policies [ 12 , 14 , 15 ], nutritional regulations [ 16 , 17 , 18 ], or policies to promote PA [ 19 , 20 ], have impacts on the health behaviour of people with and without DM.…”
Section: Introductionmentioning
confidence: 99%